KINERJA KOMISI PEMILIHAN UMUM DALAM PENETAPAN DATA DAFTAR PEMILIH TETAP (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
Strategy was act as an organization target. An organization with no strategy means it moves aimlessly. A permanent voter registration list at 2019 general election there was still plenty of trouble, such as multiple and auxiliary voter. In order to a permanent voter registration list accurated, an organization must implement three step in the strategy implementation process of formulating strategy, implementing strategy and evaluating strategy. The study used a type of qualitative research with an approach to case studied. A data collection technique of interviews and documentaries. Identified technique the informant used an impressive. The identification technique of the informant used purposive sampling where the identification of the informant chose with special consideration from the researchers, taking into account the data characteristics based on the need for analysis in this study. The study led to a conclusion that was general election strategy in a permanent voter registration list for general elections commission at the 2019 in ogan komering ulu was good result as measured by several assessment indicators, and the general elections commission strategy was optimized through formulation, execution and evaluation. At the time of determining the Permanent Voter Registration Listat the 2019 General Election, many problems were still found, such as voters who did not meet the requirements. The suggerstion given by the author is the need to change the method of determining the permanent voters list and the public and improve communication coordination and openness so that any changes in population data can be directly integrated in a short time.